Constraining non-methane VOC emissions with TROPOMI HCHO observations: impact on summertime ozone simulation in August 2022 in China - S. Feng; F. Jiang; F. Jiang; F. Jiang; T. Qian; N. Wang; M. Jia; S. Zheng; J. Chen; F. Ying; W. Ju; W. Ju (Atmospheric Chemistry and Physics, 2024)
Non-methane volatile organic compounds (NMVOC), serving as crucial precursors of O3, have a significant impact on atmospheric oxidative capacity and O3 formation. However, both anthropogenic and biogenic NMVOC emissions remain subject to considerable uncertainty. Here, we extended the Regional multi-Air Pollutant Assimilation System (RAPAS) using the ensemble Kalman filter (EnKF) algorithm to optimize NMVOC emissions in China in August 2022 by assimilating TROPOspheric Monitoring Instrument (TROPOMI) HCHO retrievals. We also simultaneously optimize NOx emissions by assimilating in situ NO2 observations to address the chemical feedback among VOCs–NOx–O3. Furthermore, a process-based analysis was employed to quantify the impact of NMVOC emission changes on various chemical reactions related to O3 formation and depletion. NMVOC emissions exhibited a substantial reduction of 50.2 %, especially in the middle and lower reaches of the Yangtze River, revealing a prior overestimation of biogenic NMVOC emissions due to an extreme heat wave. Compared to the forecast with prior NMVOC emissions, the forecast with posterior emissions significantly improved HCHO simulations, reducing biases by 75.7 %, indicating a notable decrease in posterior emission uncertainties. The forecast with posterior emissions also effectively corrected the overestimation of O3 in forecasts with prior emissions, reducing biases by 49.3 %. This can be primarily attributed to a significant decrease in the RO2+NO reaction rate and an increase in the NO2+OH reaction rate in the afternoon, thus limiting O3 generation. Sensitivity analyses emphasized the necessity of considering both NMVOC and NOx emissions for a comprehensive assessment of O3 chemistry. This study enhances our understanding of the effects of NMVOC emissions on O3 production and can contribute to the development of effective emission reduction policies.